Saúde e Discurso - (:unkn) unknown (Instituto Brasileiro de Informação em Ciência e Tecnologia, 2019)
The publication of these collections aims to show the results in an organized way. 10 years of research for a critical theorization of information, based on the Theory of Communicative Acting by Jürgen Habermas, investigating and discussing its applications, mainly in the management of complex organizations such as research institutes, universities and hospitals. It is expected to contribute to the administration of organizations, particularly with regard to process improvement and innovation. This work does part of the activities developed as a researcher at the Brazilian Institute of Information in Science and Technology – IBICT from April 2009.
Keywords: Agir Comunicativo; Discurso; Luhmann; Saúde; Ciências sociais aplicadas